Distributed finite‐time information discovery‐based secondary restoration for islanded microgrids. Issue 3 (26th February 2020) - Shrivastava, Sonam; Subudhi, Bidyadhar
Abstract : A new finite‐time secondary voltage and frequency restoration scheme for an islanded microgrid (MG) is proposed in this study. All distributed generators (DGs) do not have access to the voltage and frequency reference value which makes their control more challenging. Therefore, a finite‐time Information Discovery Scheme (IDS) is incorporated into the distributed secondary control scheme. The IDS provides local estimates of the global references of voltage and frequency for DGs in finite‐time, and distributed control scheme uses this information to restore the voltage and frequency of MG to their reference values while accurately sharing the active power among the DGs in finite‐time. The proposed control scheme is implemented on a sparse communication network and obviates the need for a central controller thereby reducing the risk of single‐point‐failure. The proof for finite‐time restoration and restoration time upper‐bound are derived using Lyapunov theory. The effectiveness of the proposed control scheme is verified through simulation of an MG test system in MATLAB/SimPowerSystem environment for sudden load variation and time‐varying communication topology. The proposed control scheme supports plug and play capability and exhibits better convergence performance and disturbance rejection than the asymptotic controller based on neighbourhood tracking error.